THE COMPARISON OF VIKOR AND MAUT METHODS IN THE SELECTION OF USED CARS - Nurul Rahmadani; Risnawati Risnawati (Jurnal Riset Informatika, 2021)
Abstract A used car is a car that has been used by other people. Choosing a used car according to the needs of the buyer is very much a consideration. Used car buyers, of course, make their choices based on several criteria. The criteria for choosing a used car include transmission, price, passenger capacity, luggage capacity, year of manufacture, color, and engine capacity. These criteria are the buyer's consideration in choosing a used car because it is not easy for those who do not understand the criteria for choosing a used car. This research aims to compare the selection of used cars with the VIKOR method (Vise Kriterijumska Optimizajica I Kompromisno Resenje) and MAUT (Multi-Attribute Utility Theory). The VIKOR method is a ranking method using a multicriteria ranking index based on a certain measure of closeness to the ideal solution. Meanwhile, the MAUT method is a multi-attribute method that usually combines measurements of different risks and benefits. The research method used is descriptive research with a quantitative approach. The results of this study can be seen that using the VIKOR and MAUT methods obtained the same results, namely A5 as the selected used car.